Honorary authorship epidemic in scholarly publications? How the current use of citation-based evaluative metrics make (pseudo)honorary authors from honest contributors of every multi-author article - Kovács, József (Journal of medical ethics, 2013)
The current use of citation-based metrics to evaluate the research output of individual researchers is highly discriminatory because they are uniformly applied to authors of single-author articles as well as contributors of multi-author papers. In the latter case, these quantitative measures are counted, as if each contributor were the single author of the full article. In this way, each and every contributor is assigned the full impact-factor score and all the citations that the article has received. This has a multiplication effect on each contributor's citation-based evaluative metrics of multi-author articles, because the more contributors an article has, the more undeserved credit is assigned to each of them. In this paper, I argue that this unfair system could be made fairer by requesting the contributors of multi-author articles to describe the nature of their contribution, and to assign a numerical value to their degree of relative contribution. In this way, we could create a contribution-specific index of each contributor for each citation metric. This would be a strong disincentive against honorary authorship and publication cartels, because it would transform the current win-win strategy of accepting honorary authors in the byline into a zero-sum game for each contributor.